DNS of three-dimensional separation in turbulent diffuser flows - Ohlsson, Johan; Schlatter, Philipp; Fischer, Paul F.; Henningson, Dan S. (Springer Proceedings in Physics, 2009)
The spectral-element method (SEM), is a high-order numerical method with the ability to accurately simulate fluid flows in complex geometries. SEM has opened the possibility to study – in great detail – fluid phenomena known to be very sensitive to discretization errors, e.g. flows undergoing pressureinduced separation [4]. Recently, Cherry et al. [1] performed experiments using Magnetic Resonance Velocimetry (MRV) of turbulent diffuser flow exhibiting unsteady three-dimensional separation at Re = 10 000 based on bulk velocity and height of the inflow duct. Two geometries with different opening angles were investigated and it was found that the flow was extremely sensitive to slight changes in the geometrical setup. To understand this sensitivity and to analyze its causes, we present a direct numerical simulation (DNS) of one of these cases (denoted by “Diffuser 1“ in [1]) by means of the SEM. Here, we focus on careful analysis of mean flow results in order to assess the quality of the simulation data.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct Numerical Simulation; Discretization Error; Friction Reynolds Number; Geometrical Setup; Magnetic Resonance Velocimetry